Supervisory approaches valued at different stages of the doctoral journey : perspectives from students in education - Haley, Aimee; Holmqvist, Mona ; 0000-0002-8734-1224 (Scandinavian Journal of Educational Research, 2026)
This study identifies supervisory approaches that doctoral students value at the beginning, middle, and end of their doctoral journey. Fifteen students enrolled at two Swedish universities in the education field were interviewed. Through the lens of transformative learning, their perspectives on six areas of supervision, which have earlier been found to be important, were analysed: (1) functional guidance, (2) domain knowledge, (3) research methodology, (4) pedagogical component, (5) relationships, and (6) contextual competence. The results show that beginner doctoral students are initially impressed by their supervisors’ domain knowledge and uncertain about their methodological knowledge. In the middle phase, they have developed their own knowledge and value approaches to the supervisory relationship more neutrally. By the end, they recognise their supervisors’ knowledge gaps and limitations and value independence and autonomy. We argue that an understanding of these matters has important implications for supervision practices and for developing future independent researchers.
Keywords: autonomy; doctoral education; research training; Supervision; transformative learning